Sosialisasi Pertolongan Pertama pada Kecelakaan (P3K) dan Cedera Olahraga Pada Guru-Guru Penjasorkes di Kec. Cimanggu Kab. Cilacap - Kusmiyati; Dian Imam Saefulah; Fahmi Wiram (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
Socialization is a process of interaction and learning carried out by a human from birth until the end of his life in a cultural society. Meanwhile, in a narrow sense, it is a learning process for humans to be able to recognize the environment they will live in in the future, both physical and social. First aid is providing immediate assistance to people suffering from illness or accidents who require basic medical treatment. Meanwhile, an accident is an event that occurs accidentally, such as a traffic accident, being stabbed by a sharp object or an injury while exercising. The aim of writing this proposal is to provide knowledge regarding first aid for accidents (P3K) and injuries that occur after sports. Know what first aid should be done when experiencing sports accidents and injuries. Seeing the extent of success in providing knowledge or outreach to the public regarding first aid for accidents (P3K) and sports injuries.